Elongation the duration of steel anode with polypyrrole modification during the electrocoagulation treatment process of electroplating wastewater. Issue 2 (April 2021) - Liu, Yunxiao; Liu, Guoshuai; Wang, Han; Wu, Peng; Yan, Qun; Vayenas, Dimitris V.
Abstract: In this study, the stainless steel (SS) plate with polypyrrole (PPy) coating was adopted as a modified anode for the electrocoagulation (EC) treatment of electroplating wastewater. It was found that the PPy/PTS (Sodium p-toluene-sulfonate) coated anode could largely prevent the anodic corrosion. With the optimized EC operating parameters as initial pH at 4, EC process at 70 min and applied current density at 30 mA cm −2, removal efficiency of zinc and nickel from the electroplating wastewater reached 99.9% and 80% respectively. In addition, corrosion inhibition efficiency attained 30% even after 10 repeated EC treatment batches. Furthermore, the successful electro-deposition of coatings with dopants could be characterized by FT-IR, SEM, EDX, and the smallest gaps between the peaks and valleys of PPy/PTS coating could be observed using AFM as well. Notably, PPy was found being adsorbed parallelly to the Fe (1 1 0) surface, whereas adsorption energy of PPy/PTS obtained from molecular dynamic simulation calculation reached the lowest as − 88.87 kJ mol −1 comparing to any other coating group. Therefore, it seemed that the PPy modified SS anode could achieve a relatively high heavy metal removal rate as well as a better protection, and accordingly would help lengthen the lifespan of the steel anode. Graphical Abstract: ga1 Highlights: Stainless steel (SS) plate with polypyrrole (PPy) coating was prepared by electrodeposition. PPy coating doped with PTS presented the better anti-corrosion performance during the EC process. Heavy metals removal and inhibition efficiency of PPy coated anode kept steady after 10 EC batches. Adsorption energy of PPy/PTS (Sodium p-toluene-sulfonate) reached the lowest as − 88.87 kJ mol −1 comparing to other groups.